HUBUNGAN RANGSANGAN TAKTIL PAPILLA MAMMAE TERHADAP KEMAJUAN PERSALINAN KALA I FASE AKTIF DI KLINIK HENNY KOTA MEDAN - MASTAIDA TAMBUN (LP2MTBM MAKARIOZ, 2019)
Childbirth is the culmination of a series of pregnancy processes. Many pregnant women feel anxious, anxious, and anxious waiting for the birth to arrive. Based on data from the Inter-Census Population Survey (SUPAS) in Indonesia the MMR has decreased from 359 / 100,000 live births (KH) in 2012 to 305 / 100.00 KH in 2015. The causes of maternal death were bleeding (35.2%), hypertension (27.1%), infection (7.3%), prolonged labor (1.8%) and abortion (4.7%). The type of research used by researchers is quantitative analytic research with cross sectional approach. The population is maternity mothers who are in the henny clinic. To find out the effect of tactile stimulation of mammary papillae on the progress of first phase active labor, which amounted to 35 women giving birth in April. The sample of this study is a saturated sample taken from the total population of women giving birth to 35 pregnant women. The majority of research results were aged 20-35 years (51.4%), 16 primipara oarity respondents, the majority of respondents were educated with high school education (42.8%), as many as 23 respondents (65.7%) had tactile stimulation. Chi square statistical test results showed that the value of p = 0.001 <0.05, meaning that there is a relationship between the tactile variable mammary tactile stimulation with the progress of labor. Conclusion there is the influence of mammary papilla tactile stimulation on the progress of active phase I labor, and it is expected that medical staff, especially midwives can improve midwifery services about normal delivery care with tactile stimulation of mammary papillae on the progress of labor in the active phase I.